Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Penguasaan Konsep Dan Keterampilan Berpikir Kreatif Siswa Pada Materi Bunyi - Susi Ismail (Peneliti.net, 2022)
This research is a CAR research (classroom action research) which aims to determine whether there is an improvement in conceptual mastery and creative thinking skills of students at SMP Negeri 2 East Halmahera after applying the Problem Based Learning (PBL) learning model. This research was carried out on students of class VII SMP, amounting to 29 students. Consisting of 14 males 15 females. From the results of this study, it was found that there was an increase in the mastery of concepts and creative thinking skills of seventh grade students of SMP Negeri 2 East Halmahera. Where the data is described as follows: Student pre-action scores of 24 students, 4 of them have adequate categories and 20 are not good. However, after taking the action in cycle I, the number of individual completeness was only obtained by 1 student or 4.17%, only 45.83% or 11 people, while the number of students who were still incomplete/not good was 50% or 12 people. While in cycle II, the number of students who have not completed/reduce improved in learning is experiencing a decrease from i12 people or 50%, to 2 people or i8.33%. Meanwhile, the students who have already achieved score i with the complete i category in learning i increased to 2 people who have i very good or 8.33%, i10 people are good or i41.67%, while the i participants are educated i with the category i is good enough or i41.67% . This result synergizes with teacher activity and student activity so that it can be concluded that the application of problem-based learning model learning (PBL) can improve conceptual mastery and creative thinking for seventh grade students of SMP Negeri 2 Halmahera Timur on sound material.